Rising mean incomes for whom? - Melanie Krause; Liang Frank Shao (Luxembourg Income Study (LIS), 2018)
Not everybody is benefiting equally from rising mean incomes. We discuss the mean-income population share (MPS), defined as the population share earning less than the mean income, as an indicator of how representative the mean income is for the mass of the population. This measure is both analytically tractable and simple to interpret to inform the public debate. We discuss its properties and estimation using micro-level and grouped income data. Our empirical application finds that MPS has risen in 13 out of 16 high- and middle-income countries in the last decades, indicating that growth has mostly not been inclusive. MPS shows a mixed correlation structure with the Gini coefficient.
Keywords: D31; C80; O40; 330; Mean-income population share; inclusive growth; parametric Lorenz function